Visual hallucinations associated with bupropion use: a case report - Korkmaz, Sevda; Kuloglu, Murat; Saglam, Sadullah; Atmaca, Murad (Kure Iletisim Grubu A S, 2012)
Bupropion is an antidepresant that acts as a norepinephrine and dopamine reuptake inhibitor and has a favorable side-effect profile. The most common side-effects of this drug include insomnia, constipation, headache and dry mouth. Unlike these side-effects, we present a case in which visual hallucinations developed during use of sustained-release bupropion in therapeutic doses.
Bupropion kullanımıyla i?lişkili görsel halüsinasyon: Bir olgu sunumu
Keywords: Bupropion; visual hallucination; side-effect